Characterization of some physicochemical, textural, and antioxidant properties of muffins fortified with hydrolyzed whey protein - Bekiroglu, Hatice; Karaman, Safa; Bozkurt, Fatih; Sagdic, Osman (WILEY, 2024)
Whey protein hydrolysates, derived from enzymatic hydrolysis of whey protein isolates or concentrates, offer enhanced bioavailability and solubility compared to intact whey protein. In this study, whey protein hydrolysates (WPHs) having different hydrolysis degrees (5%, 10%, and 15%) were produced and muffin cakes were enriched with the addition of WPHs. In general, the addition of WPHs showed a significant effect on oil and protein content while the emulsion activity was improved with the increased hydrolysis degree (HD). The degree of hydrolysis increment resulted in a significant increase in both antioxidant power and antiradical activity of the WPHs. Ferric-reducing antioxidant power and ABTS radical scavenging activity ranged between 18.83-87.27 mg TE/100 g and 211.8-5063.1 mg TE/100 g, respectively. The highest FRAP and ABTS values were recorded for the 15% HD while the lowest was for the native whey protein isolate (WPI). The induction periods giving a clear information for the oxidative stability were 1593 min for the control muffins, and it was 1654 for the muffin added with WPI. Rheological data revealed that all cake batter samples including WPHs showed viscoelastic behavior. WPHs could be efficiently used in muffin formulation to increase the biofunctional effects of the final products. The study investigated the impact of whey protein hydrolysates (WPHs) with varying degrees of hydrolysis on muffin cakes. Muffin cake samples enriched with WPHs demonstrated notable antioxidant and antiradical properties. All batter samples containing hydrolyzed whey protein exhibited an elastic gel-like texture and a soft gel structure.image
Keywords: emulsion stability; hydrolysis degree; oxidative stability; thermal properties; FUNCTIONAL-PROPERTIES; SENSORY PROPERTIES; ENZYMATIC-HYDROLYSIS; RHEOLOGICAL PROPERTIES; SOY PROTEIN; IN-VITRO; PEPTIDES; OXIDATION; BEHAVIOR; QUALITY; Food Science & Technology